Exploitation of fungal sex for biotechnology and disease control - Ashton, George David (2019)
The overall theme of work in the present thesis was to gain knowledge about aspects of the fungal sexual cycle that would allow the practical exploitation of sexual reproduction for use in biotechnology and disease control.